(untitled) (Journal of Human Sciences, 2024)
The study aimed to identify the prevailing pattern of cerebral dominance (Right , Lift ) among students of The university of Benghazi , faculties ; Literature , Engineering , Medicine , Al-Marj , the study also aimed to identify the relationship of the pattern of brain dominance, according to the variables of academic specialization, and gender , the study also aimed to uncover differences in cerebral dominance patterns attributed to the two variables of gender , and the academic specialization , and used (HBDI) scale , on a sample of (100) students , (50) students from faculties Engineering , Medicine (50) students from Literature, the study found the left pattern of cerebral dominance was the most common among students , followed by the Right pattern , and the study also found that there is a relation between the pattern of brain dominance and gender , there is no relationship between the pattern of brain dominance and academic specialization , and there no difference in the pattern of brain dominance due to according to the variables of academic specialization , and gender.